2014
DOI: 10.1073/pnas.1315374111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a conserved branched RNA structure that functions as a factor-independent terminator

Abstract: Anti-Q is a small RNA encoded on pCF10, an antibiotic resistance plasmid of Enterococcus faecalis, which negatively regulates conjugation of the plasmid. In this study we sought to understand how Anti-Q is generated relative to larger transcripts of the same operon. We found that Anti-Q folds into a branched structure that functions as a factor-independent terminator. In vitro and in vivo, termination is dependent on the integrity of this structure as well as the presence of a 3′ polyuridine tract, but is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Therefore, in view of the above discussed contradictory evidences about the functionality of I-shaped terminators in vivo 26 27 28 , T tsaD is defined as an I-shaped hairpin-like cis -regulatory element that might bring about reduction in transcription by acting as a pause signal and facilitating fraying of the elongation complex or by enabling factor-dependent termination after slowing down the complex in vivo 29 or might influence transcriptional/post-transcriptional regulation of downstream genes by some other mechanism. Recently, a unique branching structure (with a trailing U-tract) was shown to function as an intrinsic terminator in Enterococcus faecalis 30 , sustaining the suggestion that greater flexibility might exist in the design of intrinsic terminator-type regulatory elements than has been contemplated so far.…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, in view of the above discussed contradictory evidences about the functionality of I-shaped terminators in vivo 26 27 28 , T tsaD is defined as an I-shaped hairpin-like cis -regulatory element that might bring about reduction in transcription by acting as a pause signal and facilitating fraying of the elongation complex or by enabling factor-dependent termination after slowing down the complex in vivo 29 or might influence transcriptional/post-transcriptional regulation of downstream genes by some other mechanism. Recently, a unique branching structure (with a trailing U-tract) was shown to function as an intrinsic terminator in Enterococcus faecalis 30 , sustaining the suggestion that greater flexibility might exist in the design of intrinsic terminator-type regulatory elements than has been contemplated so far.…”
Section: Resultsmentioning
confidence: 87%
“…In bacteria, REP-containing regions are transcribed [16, 17], but they form stem-loop-like structures that could prematurely terminate transcription [18]. To rule out this possibility, we performed a 3′ RACE assay, which confirmed that full-length MgrR was produced when E.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, expression of functional sRNAs may be more dependent on RNA chaperones and/or processing factors, as well as cis‐acting sequence elements at their transcriptional boundaries that are difficult to define at (Chae et al, ; Moores et al, ; Morita et al, ; Kriner, Sevostyanova, & Groisman, ; Shiflett et al, ). Although RNA chaperones have yet to be identified in mycobacteria, the roles of extended native 3′ sequences for expression of mycobacterial sRNAs warrant further investigation to determine whether mcr11 is exceptional or representative of a larger group of sRNAs with regards to expression and stability requirements (Ishikawa, Otaka, Maki, Morita, & Aiba, ; Johnson et al, ; Moores et al, ; Regnier & Hajnsdorf, ; Sauer & Weichenrieder, ; Shiflett et al, ; Olejniczak & Storz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although RNA chaperones have yet to be identified in mycobacteria, the roles of extended native 3′ sequences for expression of mycobacterial sRNAs warrant further investigation to determine whether mcr11 is exceptional or representative of a larger group of sRNAs with regards to expression and stability requirements (Ishikawa, Otaka, Maki, Morita, & Aiba, 2012;Johnson et al, 2014;Moores et al, 2017;Regnier & Hajnsdorf, 2013;Sauer & Weichenrieder, 2011;Shiflett et al, 2003;Olejniczak & Storz, 2017).…”
Section: Mechanism Of Mcr11 Transcriptional Terminationmentioning
confidence: 99%